2016
DOI: 10.1007/s00737-016-0647-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin level measured 48 h after delivery is associated with development of postpartum depressive symptoms: a 3-month follow-up study

Abstract: The aim of this study was to assess the possible relationship between leptin status and postpartum depressive symptoms using serum levels of leptin collected 24-48 h after delivery in a cohort Chinese sample. Women delivering a full-term, singleton, and live-born infant in the period from August 2013 to March 2014 were enrolled immediately postpartum. A blood sample was obtained 24-48 h after childbirth to test serum levels of leptin. Participation consisted of a visit in an obstetric unit at 3 months after de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Due to its role in adiposity, leptin has consistently been correlated with body mass index (BMI) and waist circumference (e.g. Jow et al, 2006;Morris et al, 2012;Chen et al, 2016). Leptin has also been related to risk factors for cardiovascular disease, with elevated leptin levels associated with higher systolic and diastolic blood pressure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its role in adiposity, leptin has consistently been correlated with body mass index (BMI) and waist circumference (e.g. Jow et al, 2006;Morris et al, 2012;Chen et al, 2016). Leptin has also been related to risk factors for cardiovascular disease, with elevated leptin levels associated with higher systolic and diastolic blood pressure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We used a cut-off of ≥12 in this study. We used the Chinese version of the EPDS, which has been verified and frequently used in previous studies [ 34 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…While the first of these two studies 71 also examined leptin levels and found no concurrent relationship with postpartum depression, others have reported that reduced serum leptin after delivery predicts the later development of postpartum depression 72 .…”
Section: Depression and Inflammation In The Perinatal Periodmentioning
confidence: 99%
“…Regarding adipokines in perinatal depression, lower adiponectin levels have been associated with postpartum depression by at least one group 71 ; however a second group that followed women throughout pregnancy and the postpartum period did not observe this association 55 . While the first of these two studies 71 also examined leptin levels and found no concurrent relationship with postpartum depression, others have reported that reduced serum leptin after delivery predicts the later development of postpartum depression 72 .…”
Section: Depression and Inflammation In The Perinatal Periodmentioning
confidence: 99%